PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP KINERJA KARYAWAN DEPARTEMEN QUALITY CONTROL PT MCDERMOTT BATAM - Moh Nasir; Daris Purba (Bajang Institute, 2025)
This study aims to analyze the influence of competence and training on employee performance in the Quality Control Department of PT McDermott Batam. A quantitative associative approach was employed, with data collected from 73 respondents and analyzed using validity tests, reliability tests, normality tests, t-tests, F-tests, and determination coefficients through SPSS software. The results indicate that both competence and training have a significant partial and simultaneous effect on employee performance. The coefficient of determination value of 66.7% suggests that competence and training substantially influence employee performance, while the remaining 33.3% is attributed to other factors not examined in this study.